1983
DOI: 10.1016/0167-2584(83)90031-2
|View full text |Cite
|
Sign up to set email alerts
|

Anodic oxide films of nickel in alkaline electrolyte

Abstract: Cyclic voltammetryand ellipsometry were applied to investigate the growth and nature of the anodic oxide film on nickel in O.lM KOH. At prereduced nickel a poorly conducting oxide IS formed which grows with constant refractive index in the potential range up to about 1 V. At higher potentials the changes in the ellipsometric parameters $ and A indicate a conversion into a good conducting oxide. By repeated oxidation and reduction a thicker oxide film is grown at the surface, this oxide is not identical with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In addition to α-Ni(OH)2 discussed above, some works mention possible formation of NiO species sandwiched between the metal and the outer layer of α-Ni(OH)2. 23,68,69 The amount of NiO formed during potential cycling in the low-potential region can be considered insignificant, as evidenced by in situ…”
Section: α-Ni(oh)2 Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to α-Ni(OH)2 discussed above, some works mention possible formation of NiO species sandwiched between the metal and the outer layer of α-Ni(OH)2. 23,68,69 The amount of NiO formed during potential cycling in the low-potential region can be considered insignificant, as evidenced by in situ…”
Section: α-Ni(oh)2 Formationmentioning
confidence: 99%
“…Such changes are reproducible and have been reported in several publications. 41,64,68,[73][74][75][76][77][78][79] The peak potential and the corresponding current density significantly depend on the surface state of the electrode, as well as on the cathodic potential limit of the CV. 50,76,79 The origin of that second anodic peak is still debated, some authors attributing it to the formation of Ni-OHad,, 48,64 the other -to the oxidation of adsorbed/absorbed hydrogen, 41,73,74,80 as discussed below.…”
Section: α-Ni(oh)2 Formationmentioning
confidence: 99%
“…Ni(OH) 2 also forms electrochemically on Ni electrodes in alkaline media, which has importance for the development of Ni-based electrocatalysts [23,105,179,[184][185][186][187]. Consequently, the surface electrochemistry has been extensively studied using atomic force microscopy [188], ellipsometry [181,[189][190][191], IR spectroscopy [192], Raman spectroscopy [166,193,194], UV-Vis spectroscopy [192,195], voltammetry [179,185,[196][197][198][199][200][201], X-ray scattering [176], XPS [179,202] and gravimetry with an electrochemical quartz crystal microbalance [203,204]. During a forward voltammetric sweep, a surface bilayer of α-Ni(OH) 2 underlaid by NiO x forms initially [179].…”
Section: (D) Chemical Ageingmentioning
confidence: 99%
“…On the basis of the XPS peak shapes and positions, the hydroxide layer is assessed to be α-Ni(OH) 2 [179]. Ni(OH) 2 is also a common component of the passive layers and corrosion deposits on Ni metal [176,180,181] and Ni-containing alloys [182,183] that form in alkaline (e.g. [176]) and neutral media (e.g.…”
Section: (D) Chemical Ageingmentioning
confidence: 99%
“…In alkaline media, NiO or a mixture of NiO and Ni 3 O 4 oxides is formed, which are further oxidized to NiO 2 at more noble potentials. Other researchers have found the initial film to be a thin layer of NiO· n H 2 O, which is later transformed into Ni (OH) 2 or β‐NiOOH . It can be concluded that the presence of specific anions, especially chloride ions, destroys passivity and leads to local corrosion attack …”
Section: Introductionmentioning
confidence: 99%